Трактовки термина "система" - Дольская, Ольга Алексеевна (НТУ "ХПИ", 2015)
При осуществлении системного анализа достаточно частой является ошибка смешение трактовок изучения системы, что приводит к парадоксальным ошибкам – неумению выбрать определенный аспект ее описания. Сегодня актуализируется необходимость очертить те философские аспекты изучения системы, которые дадут возможность уяснить смысловое значение каждого из них и не смешивать их при обсуждении проблем, связанных с изучением системы. Статья знакомит читателя с возможными трактовками термина "система". Любой фрагмент реальности, мышление, технические фрагменты могут выступать в виде систем. Различные трактовки «задают» категориальный аппарат описания системы.

The article acquaints a reader with possible interpretations of term system. There are a few interpretations. It allows to select the proper aspects of description of the system. The presence of interpretations is related to the unlimited amount of the various systems. Any fragment of reality, thought, technical fragments can come forward as the systems. Different interpretations "set" the category vehicle of description of the system. During realization of systems analysis the enough frequent is error mixing of interpretations of study of the system, that results in paradoxical errors – lack of ability to choose the certain aspect of its description. A necessity to outline those philosophical aspects of study of the system, which will give possibility to get a clear idea of the semantic value of each of them and not mix up them at the discussion of the problems related to the study of the system, Becomes actual today.
Interpretation of the term "system"
Keywords: онтологическая трактовка; система; эпистемологическая трактовка; социально-антропологическая трактовка; искусственно-техническая трактовка; эпистемологическо-методологическая трактовка; ontological interpretation; gnoseological interpretations of the system; socially-anthropological interpretations of the system; artificially-technical system